Crowdsourced Data for Physical Activity-Built Environment Research: Applying Strava Data in Chengdu, China - Yang, Linchuan; Yu, Bingjie; Liang, Pengpeng; Tang, Xianglong; Li, Ji (Frontiers in Public Health, 2022)
The lack of physical activity has become a rigorous challenge facing many countries. The relationship between physical activity and the built environment is a hot research topic in recent decades. This study applies Strava Heatmap in December 2021 in central Chengdu, from which we extract the spatial thermal distribution of cycling and running tracks, and develops spatial regression models for numerous 500 m × 500 m grids (N=2788) to assess different impacts of the built environment on cycling and running (two types of physical activity). The findings are as follows: (1) Land-use diversity has no significant effects on the physical activity of residents, which largely differs from the majority of the evidence gathered from studies. (2) Road density, water area, greenland area, number of sports venues, and number of companies are observed to significantly facilitate cycling and running; (3) the river line and the light index have positive associations with running, but not cycling; (4) housing price is positively correlated with running and cycling indexes; and (5) schools and other educational facilities with numerous sports venues seem to discourage the above two types of physical activities owing to the enduring influence of the COVID-19 pandemic. This study provides a theoretical basis and policy implications (e.g., healthy community construction and green space area planning) for urban planners, practitioners, and policy-makers.